Pembelajaran Synectics Realistik Berbantuan Schoology untuk Meningkatkan Kemampuan Literasi Matematika Siswa - Nur Hidayat, Yodie (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
The aim of this research is (a) to determine whether students' mathematical literacy abilities using schoology-assisted realistic synectics learning are better than those using conventional learning (PBL) (b) to find out schoology-assisted realistic synectics learning on students' mathematical literacy abilities. The subjects in this research were 32 students in class VII B of SMP Negeri 4 Adiwerna in the 2022/2023 academic year, with samples taken using random sampling techniques. Quantitative data analysis was tested using the t test, proportion test and gain test. The final result of learning students' mathematical literacy skills using realistic synectics learning assisted by classical schoology was 75%; the classical completion of the group with realistic synectics learning assisted by schoolology was better than the group with scientific PBL learning; The increase in students' mathematical literacy skills with realistic synectics learning assisted by schoolology is higher than the increase in students' mathematical literacy skills taught by PBL scientific.